The birth of the new justice the internationalization of crime and punishment, 1919-1950 - Lewis, Mark 1968- (Oxford studies in modern European history, 2014)
'The Birth of the New Justice' is a history of the attempts to instate ad hoc and permanent international criminal courts and new international criminal laws from the end of World War I to the beginning of the Cold War. The purpose of these courts was to repress aggressive war, war crimes, terrorism, and genocide